Pengaruh advertising dan promosi sebagai strategi brand building terhadap brand awareness (studi pada tokopedia) - Rana rachmatul kristian; Shinta Dewi Aulia Sari; Muhammad Abdul Muid; M,Cholilur Rochman; Mohammad Ali Ridho; Rahmat Riko Za’fan Ispriadi (CV. ITTC INDONESIA, 2026)
The increasingly intense competition among digital marketplaces requires companies to implement effective marketing strategies in order to build and maintain brand awareness in consumers’ minds. Advertising and promotion are essential components of brand building strategies that are believed to influence consumers’ brand awareness. This study aims to analyze the effect of advertising and promotion as brand building strategies on brand awareness at Tokopedia.This study employs a quantitative approach with an associative research design and a survey method. The population of this study consists of Tokopedia users, with a sample of 50 respondents selected using purposive sampling techniques. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using validity tests, reliability tests, and multiple linear regression analysis.The results show that the correlation coefficient (R) is 0.649 and the coefficient of determination (R²) is 0.422. These findings indicate that advertising and promotion simultaneously explain 42.2% of the variation in brand awareness, while the remaining 57.8% is influenced by other variables outside the research model. The simultaneous test results reveal that advertising and promotion have a significant effect on brand awareness. However, the partial test results indicate that each variable does not have a significant individual effect at the 5% significance level.In conclusion, the combination of advertising and promotion strategies plays an important role in building Tokopedia’s brand awareness. Therefore, companies are encouraged to manage these strategies in an integrated manner to enhance competitiveness in the digital marketplace.